Carbohydrate-binding protein from stinging nettle as fusion inhibitor for SARS-CoV-2 variants of concern - Vanhulle, Emiel; D’huys, Thomas; Provinciael, Becky; Stroobants, Joren; Camps, Anita; Noppen, Sam; Schols, Dominique; Van Damme, Els J. M.; Maes, Piet; Stevaert, Annelies; Vermeire, Kurt (Frontiers in Cellular and Infection Microbiology, 2022)
Urtica dioica agglutinin (UDA) is a carbohydrate-binding small monomeric protein isolated from stinging nettle rhizomes. It inhibits replication of a broad range of viruses, including coronaviruses, in multiple cell types, with appealing selectivity. In this work, we investigated the potential of UDA as a broad-spectrum antiviral agent against SARS-CoV-2. UDA potently blocks transduction of pseudotyped SARS-CoV-2 in A549.ACE2+-TMPRSS2 cells, with IC50 values ranging from 0.32 to 1.22 µM. Furthermore, UDA prevents viral replication of the early Wuhan-Hu-1 strain in Vero E6 cells (IC50 = 225 nM), but also the replication of SARS-CoV-2 variants of concern, including Alpha, Beta and Gamma (IC50 ranging from 115 to 171 nM). In addition, UDA exerts antiviral activity against the latest circulating Delta and Omicron variant in U87.ACE2+ cells (IC50 values are 1.6 and 0.9 µM, respectively). Importantly, when tested in Air-Liquid Interface (ALI) primary lung epithelial cell cultures, UDA preserves antiviral activity against SARS-CoV-2 (20A.EU2 variant) in the nanomolar range. Surface plasmon resonance (SPR) studies demonstrated a concentration-dependent binding of UDA to the viral spike protein of SARS-CoV-2, suggesting interference of UDA with cell attachment or subsequent virus entry. Moreover, in additional mechanistic studies with cell-cell fusion assays, UDA inhibited SARS-CoV-2 spike protein-mediated membrane fusion. Finally, pseudotyped SARS-CoV-2 mutants with N-glycosylation deletions in the S2 subunit of the spike protein remained sensitive to the antiviral activity of UDA. In conclusion, our data establish UDA as a potent fusion inhibitor for the current variants of SARS-CoV-2.